Function of the priest’s door in the medieval churches in Finland - Löija, Pauli (Hikuin, 1995)
The intention of my paper is to introduce some aspects which illustrate the function of the priest’s door in the medieval churches of Finland. This paper does not include churches of which I did not get complete information, but it includes fourchurches which are today in ruins (Mustasaari [Korsholm], Pålkåne, Rauma [Raumo], Vihti [Vichtis]),' and also one church which is totally destroyed (Saloinen in Raahe). It was possible to include these churches because I was able to get all the necessary information about them. also included the church of Alatornio (Nedertorneå) in Tornio (Torneå) in my study, although it did not belong to the medieval diocese of Turku (Abo). Then there are two churches (Foglo and Hammarland) which I had to count twice, because the situation of the priest’s door and the chancel in these churches had changed in medieval times, so that both of them could be counted as two. Also the churches of Porvoo (Borgå) and Inkoo (Inga) changed totally in medieval times, but there is no information left about their former state. The cathedral of Turku I had to count as three because of its changes in medieval times.5 The total number of the churches studied for this paper is then 82.